2018
DOI: 10.1002/chir.22810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metalaxyl enantiomers stress on root activity and leaf antioxidant enzyme activities in tobacco seedlings

Abstract: The objective of this experiment was to study the effects of metalaxyl enantiomers on the activity of roots and antioxidative enzymes in tobacco seedlings. Water culture experiment was conducted to analyze the effects of different concentrations of metalaxyl enantiomers (30 and 10 mg L ) on root activity and leaf superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities and malondialdehyde (MDA) content of tobacco seedlings. The results showed that metalaxyl significantly inhibited root activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…These findings suggest that EBR plays an important role in alleviating the harmful effects of suboptimal RZT by regulating root activity and bleeding rate in cucumber seedlings. The results are consistent with those of earlier studies, which found that RZT significantly affected plant biomass, bleeding rate, and root activities [1, 55]. Moreover, suboptimal RZT both increases root oxygen demand and decreases oxygen concentration available in soil, which can result in hypoxic conditions and reduce root and shoot growth [56].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that EBR plays an important role in alleviating the harmful effects of suboptimal RZT by regulating root activity and bleeding rate in cucumber seedlings. The results are consistent with those of earlier studies, which found that RZT significantly affected plant biomass, bleeding rate, and root activities [1, 55]. Moreover, suboptimal RZT both increases root oxygen demand and decreases oxygen concentration available in soil, which can result in hypoxic conditions and reduce root and shoot growth [56].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study suggested that low root zone temperature caused a significant reduction in root activity, thus leading to a significant reduction in growth [54]. Root activity reflects the strength of all metabolic processes in the root system, including respiration, oxidation, and enzyme activities, and nutrient absorption and translocation from roots to shoots, which are closely related to all developmental processes [55]. Our results demonstrated that, LT treatment severely reduced root activity and bleeding rate, while these significantly increased in cucumber seedlings treated with exogenous EBR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to Ji's (2011) study, which showed that after 40 h of treatment with Lactarius vellereus fermentation liquid extract, the activities of SOD and CAT of Alternaria alternata decreased rapidly to the minimum (0.828 U•g −1 , 0.012 U•g −1 •s −1 , respectively) [54]. Our results were also similar with other reports: Ibrahim et al (2018) discovered that high salinity significantly reduced SOD activity of wheat (Triticum aestivum) [55]; Yan et al (2006) found that CAT activity of liquorice (Glycyrrhiza uralensis) decreased under salt and drought stress [56]; and Fang et al (2018) found that metalaxyl significantly inhibited root activity and significantly improved leaf SOD, POD, and CAT activities and MDA content in tobacco (Nicotiana tabacum) seedlings [57]. Apparently, application of the alkaloids triggered a series of physiological shifts in the seedlings to prepare for the stress, which was expressed in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…Superoxide dismutase (SOD) activity was detected using the p-nitro blue tetrazolium chloride photochemical reduction method [18]. Peroxidase (POD) activity was determined using the guaiacol method [19].…”
Section: Physiological Index Of Cadmium Stressmentioning
confidence: 99%